Pro-inflammatory cytokines and depression in myocardial infarction - O. L. Barbarash; N. B. Lebedeva; V. N. Karetnikova; S. A. Berns; V. V. Kashtalap; L. S. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To assess the associations between inflammatory factors and anxiety (A) and depression (D) levels in patients with myocardial infarction (MI). Material and methods. The study included 100 MI patients, hospitalised with a diagnosis of Q-wave MI (mean age 62,0±1,3 years). The methods of psychosocial status assessment included Zung depression scale and SpielbergerKhanin personal and reactive anxiety scales. The inflammatory markers of interest included interleukins (IL) 1-beta, IL-6, IL-8, IL-10, and C-reactive protein (CRP). Results. D and A symptoms in the early post-MI stage were associated with higher risk of cardiovascular events in the following year. Among MI patients with comparable MI severity, D and A symptoms were linked to higher levels of pro-inflammatory cytokines IL-1-beta, IL-8, IL-8, and INF-gamma. Conclusion. In MI patients with D and A symptoms, one of the mechanisms of poor prognosis is an activation of subclinical inflammation.